Remediation of surface water contaminated by pathogenic microorganisms using calcium peroxide: Matrix effect, micro-mechanisms and morphological-physiological changes. (1st March 2022) - Qiu, Wenhui; Chen, Honghong; Zhang, Shuwen; Xiong, Ying; Zheng, Ming; Zhu, Tingting; Park, Minkyu; Magnuson, Jason T.; Zheng, Chunmiao; El-Din, Mohamed Gamal
Highlights: Low levels of CaO2 effectively inactivated pathogenic bacteria and virus. HRS (OH −, OH, H2 O2, and O2 − ) accounted for pathogens inactivation. [HRS]SS and their reaction rate constants was determined for micromechanism model. Environment-level ions and DOM may influence pathogens inactivation. Bactria and virus underwent morphological and physiological changes. Abstract: Calcium peroxide (CaO2 ), a common solid peroxide, has been increasingly used in contaminated site remediation due to its ability to release oxygen (O2 ) and hydrogen peroxide (H2 O2 ) and its environmental friendliness. Our present study is first to explore micromechnisms of CaO2 to efficaciously inactivate pathogen indicators including gram-negative bacterium of Escherichia coli ( E. coli ), gram-positive bacterium of Staphylococcus aureus ( S. aureus ), and virus of Escherichia coli -specific M13 bacteriophage ( VCSM13 ) under low concentration (≤ 4 mmol L −1 (mM)). The inactivation mechanisms of E. coli, S. aureus (1 mmol L −1 CaO2 ) and VCSM13 (4 mmol L −1 ) were mainly attributed to OH − (32∼58%) and OH (34∼42%), followed by H2 O2 (13∼20%) and O2 − (10∼12%) generated from CaO2, with the observed morphological and physiological-associated damages. Also, average steady-state concentrations of (OH −, OH, H2 O2, and O2 − ) and their reaction rate constants with E. coli and VCSM13 were determined. Accordingly, the micro-mechanism model of inactivation was established and validated, and the inactivation efficiency of the same order of magnitude of pathogen was predicted. Furthermore, during the common environmental factors, the copper ions was found to be promote CaO2 inactivation of pathogens, and dissolved organic matter (DOM) fractions had a negative effect on CaO2 inactivation. The present study explored the mechanisms of CaO2 inactivation of pathogens in real surface water, laying the foundation for its potential use in the inactivation of water-borne microbial pathogens. Graphical abstract: Image, graphical abstract